A balance of Yki/Sd activator and E2F1/Sd repressor complexes controls cell survival and affects organ size - Zhang, Peng; Wang, Xi; Xiang, Jinyi; Cheng, Yong-Sheng; Marchetti, Marco; Edgar, Bruce (Developmental cell, 2017)
Summary: The Hippo/Yki and RB/E2F pathways both regulate tissue growth by affecting cell proliferation and survival, but interactions between these parallel control systems are poorly defined. In this study, we demonstrate that interaction between Drosophila E2F1 and Sd disrupts Yki/Sd complex formation and thereby suppresses Yki target gene expression. RBF modifies these effects by reducing E2F1/Sd interaction. This regulation has significant effects on apoptosis, organ size, and progenitor cell proliferation. Using a combination of DamID-seq and RNA-seq, we identified a set of Yki targets that play a diversity of roles during development and are suppressed by E2F1. Further, we found that human E2F1 competes with YAP for TEAD1 binding, affecting YAP activity, indicating that this mode of cross-regulation is conserved. In sum, our study uncovers a previously unknown mechanism in which RBF and E2F1 modify Hippo signaling responses to modulate apoptosis, organ growth, and homeostasis.
Available online 4 December 2017
Gesehen am 31.07.2018